2015
DOI: 10.5539/gjhs.v7n6p295
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Comparative Advantage and Intra-Industry Trade in the Pharmaceutical Industry of Iran

Abstract: Background:Drug costs in Iran accounts for about 30% of the total health care expenditure. Moreover, pharmaceutical business lies among the world’s greatest businesses. The aim of this study was to analyze Iran’s comparative advantage and intra-industry trade in pharmaceuticals so that suitable policies can be developed and implemented in order to boost Iran’s trade in this field.Methods:To identify Iran’s comparative advantage in pharmaceuticals, trade specialization, export propensity, import penetration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…However, a study entitled "the impact of exchange rate fluctuations on the import of medical equipment in Iran" was carried out by Jalaei and Jafari who reported that GDP and oil revenues have positive impacts on the import of medical equipment while exchange rate fluctuations had a negative effect on the same variable (28). Moreover, in another study conducted by Yusefzadeh et al (10) on the business inside the medicine industry in Iran, it Shiraz E-Med J. 2018; 19(10):e66512.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study entitled "the impact of exchange rate fluctuations on the import of medical equipment in Iran" was carried out by Jalaei and Jafari who reported that GDP and oil revenues have positive impacts on the import of medical equipment while exchange rate fluctuations had a negative effect on the same variable (28). Moreover, in another study conducted by Yusefzadeh et al (10) on the business inside the medicine industry in Iran, it Shiraz E-Med J. 2018; 19(10):e66512.…”
Section: Discussionmentioning
confidence: 99%
“…The medicine costs have experienced an increase in Iran, as well as some other countries, and these costs comprise about 30% of all health care costs and 50% of other costs in this realm (10). The analysis of the pharmaceutical industry in Iran indicated that from 1997 to 2010, the medicine use and consumption had 28.38% increases each year.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement results in variation from 0 to 100. This equation is the IIT Grubel-Lloyd Index which later are being used broadly by researchers in looking for the level of IIT between advanced countries and developing countries including IIT in the ASEAN region, and as the measurement of the intensity of trade integration (Yusefzadeh et al, 2015). Krugman (2015) explained the phenomena for IIT product differentiation, increasing returns to scale, and monopolistic competition as an approach for the imperfect market structure.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, the Iran Food and Drug Administration (IFDA) reported that the funds allocated to API and end products was about US$ 1 million (42%) and US$ 1.4 million (58%), respectively [ 21 ]. Although efforts have been made in recent years to reduce the amount of currency allocated to medicines, all such efforts have demonstrated Iran’s dependence on foreign countries in the field of pharmaceutical manufacture [ 25 ]. For example, one analysis of data from the Central Bank of Iran (CBI), published by Iran Open Data, shows that approximately US$ 43.8 billion in government-subsidized funds were earmarked for the import of essential goods, with nearly US$ 4.2 billion allocated to pharmaceutical companies as a preferential currency (42,000 Iranian rial) in the 2 years leading up to 2020 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%